Design of a resonant magnetic perturbation ELM suppression system for JET - Agarici, G.; Becoulet, M.; Nardon, E.; Saille, A.; Thomas, P.R.; Verger, J.M. (Fusion engineering and design, 2007)
The suppression of ELMs with a resonant magnetic perturbation (RMP), as demonstrated in DIIID experiments [T. Evans, et al., Suppression of large edge localized modes with edge resonant magnetic fields in high confinement DIII-D plasmas, Nucl. Fusion 45 (2005) 595–607 [1]], and widely published [K.H. Burrell, et al., Plasma Phys. Control., Fusion 47 (2005) B37–B52 [2]; M. Becoulet, et al., Edge localized modes control by stochastic magnetic field, Nucl. Fusion 45 (2005) 1284–1292 [3]], is an attractive solution to the problem of divertor target erosion in ITER. Ideally, the RMP should be strong at the plasma edge and weak in the core, which requires the installation of the RMP coils as close as possible to the plasma. In both ITER and JET, an installation of the RMP coils within the vacuum vessel would subject the coils to neutron irradiation, tritium contamination and all the problems of furnishing cooling and electrical services, across many interfaces. So for JET, it has been proposed to install an “ITER prototype” RMP system located ex-vessel.